On the Relationship between College Students’ Entrepreneurship Education and Regional Economic Development - Li, Junjie (Journal of Theory and Practice of Social Science, 2023)
The development of regional economy needs high-quality entrepreneurial talents with innovative spirit as the support and innovation development as the fundamental driving force. As an important base for cultivating innovative talents, colleges and universities carry out relevant entrepreneurship education for ft students in order to integrate them with the society and meet the requirements and needs of the rapid development of the society, so as to cultivate students' entrepreneurial ability, entrepreneurial spirit and innovative consciousness and become a driving force for regional economic development. The development of local economy can also provide more platforms and opportunities for college students who have just entered the ft campus to exercise, which can complement and promote each other. Universities and enterprises in different parts of the country should strengthen cooperation, build an integrated platform of learning, production and construction, strengthen the construction of training bases for college students' entrepreneurial practice, and improve their professional quality and ability in practice. Based on this, this paper studies the relationship between college students' entrepreneurship education and regional economic development.